Contrast Reversal in Scanning Tunneling Microscopy and Its Implications for the Topological Classification of SmB6. Issue 10 (30th January 2020) - Herrmann, Hannes; Hlawenka, Peter; Siemensmeyer, Konrad; Weschke, Eugen; Sánchez‐Barriga, Jaime; Varykhalov, Andrei; Shitsevalova, Natalya Y.; Dukhnenko, Anatoliy V.; Filipov, Volodymyr B.; Gabáni, Slavomir; Flachbart, Karol; Rader, Oliver; et al.
Abstract: SmB6 has recently attracted considerable interest as a candidate for the first strongly correlated topological insulator. Such materials promise entirely new properties such as correlation‐enhanced bulk bandgaps or a Fermi surface from spin excitations. Whether SmB6 and its surface states are topological or trivial is still heavily disputed however, and a solution is hindered by major disagreement between angle‐resolved photoemission (ARPES) and scanning tunneling microscopy (STM) results. Here, a combined ARPES and STM experiment is conducted. It is discovered that the STM contrast strongly depends on the bias voltage and reverses its sign beyond 1 V. It is shown that the understanding of this contrast reversal is the clue to resolving the discrepancy between ARPES and STM results. In particular, the scanning tunneling spectra reflect a low‐energy electronic structure at the surface, which supports a trivial origin of the surface states and the surface metallicity of SmB6 . Abstract : Samarium hexaboride is proposed to be the first example of a topological Kondo insulator, a new class of materials at the intersection of topological insulators and heavy fermions. Results from both angle‐resolved photoemission and scanning tunneling microscopy, previously considered to be incompatible, can be understood in terms of an alternative explanation for the unusual surface conductivity of SmB6 .